ANALYSIS OF INFLUENCE FACTORS SOCJOGRAPHIC AND DEMOGRAPHIC OF THE LEVEL EMPATHIC NURSING STUDENTS - Rachubińska, Kamila; Stanisławska, Marzanna; Grochans, Elżbieta; Robaszkiewicz, Renata; Jurczak, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction: Empathy calls for selfless concern for the other person and strengthens pro-social attitudes. Empathy in nursing gives for the patient a feeling of being understood and accepted, and ensures safe proximity and share their problems. Aim: The aim of the study is rating influence demographic and socjographic factors on the level of empathic understanding of nursing students. Material and Methods: The study included 322 nursing students I ° and II ° Pomeranian Medical University in Szczecin, in 2015. The research tool was a questionnaire consisting of two parts. The first part concerned the data socjograficznych and demographics. The second part was a questionnaire Understanding empathy Other People (KRE) by Andrzej Węglińskiego. Results and conclusions: Nursing students present average level of empathic understanding. When older the age, empathic understanding is weaker. Women have a higher level of empathic understanding (65 pts.) than men (56 pts.). Symptom: willingness to sacrifice for the other was significantly higher in persons who are in a relationship (p <0.05, 12), relative to those of free (11.4). The level of understanding of empathy does not depend significantly on the place of residence and year of study (p> 0.05).